Construction of a ternary MoO2/Ni/C hybrid towards lithium-ion batteries as a high-performance electrode. (26th July 2022) - Shen, Jian; Duan, Guangbin; Guo, Xi; Yang, Guangxu; Li, Li; Cao, Bingqiang
Abstract : The high lithium storage performance of 3D flower-like MoO2 /Ni/C through a temperature annealing strategy is benefitted from the high capacitive contribution, high electrical conductivity, and good structural stability. Abstract : Although the advantages of transition metal oxides (TMOs) include low cost, convenient synthesis and high capacity, the severe volume expansion and modest conductivity restrain their extensive applications. In this work, we introduced carbon sources into MoO2 /Ni materials by high temperature annealing, and successfully obtained MoO2 /Ni/C composites with a three-dimensional (3D) flower-like structure. In addition, the outermost carbon coating can efficaciously boost the electrical conductivity of the MoO2 /Ni/C and buffer its volumetric expansion. As expected, the MoO2 /Ni/C sample shows a high lithium storage capacity of 808 mA h g −1 after 200 cycles at 200 mA g −1 when utilized as a lithium-ion battery (LIB) anode. Therefore, it also provides guidance for the construction and optimization of carbon-coated TMO anode materials for LIBs.